Measuring data quality for ongoing improvement : a data quality assessment framework - Sebastian-Coleman, Laura (Data quality author and practitioner) (Morgan Kaufmann Series on Business Intelligence., 2013)
The Data Quality Assessment Framework shows you how to measure and monitor data quality, ensuring quality over time. You'll start with general concepts of measurement and work your way through a detailed framework of more than three dozen measurement types related to five objective dimensions of quality: completeness, timeliness, consistency, validity, and integrity. Ongoing measurement, rather than one time activities will help your organization reach a new level of data quality. This plain-language approach to measuring data can be understood by both business and IT.